Preliminary results of tomotherapy for treatment of inoperable recurrent non-small cell lung cancer at bronchial stump site after right pneumonectomy - Seok Jang, Hong; Kwon Moon, Seong (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : This study aimed to prospectively investigate the clinical outcomes of curative radical helical tomotherapy (HT) applied to recurrent non-small cell lung cancer (NSCLC) at the bronchial stump site after right pneumonectomy. After right pneumonectomy, the heart shifted right laterally. The chambers of the heart closed with a recurrent mass at the bronchial stump were the right atrium and left atrium due to right shifting of the heart. The unfavorable bronchial stump recurrent cancer-heart geometry due to a right shift of the heart might serve as a reliable predictor of cardiac morbidity for aggressive radiotherapy. Material and methods : The 23 patients received HT for the recurrent NSCLC at the bronchial stump site after right pneumonectomy between 2008 and 2011. The median age of the patients was 65 years (range 56–74). Results : We prescribed 95% volume of the primary planning target volume (PTV) to a total dose of 69 Gy in 30 fractions, and 95% of the secondary PTV to a total dose of 54 Gy in 30 fractions with reduction of the 50% volume of the heart < 20 Gy. The median conformal index in the 23 plans was 1.21. The mean fraction of primary PTV receiving more than 95% of the prescribed dose was 97.8%. The mean V45, V50, V60 of the heart were 10.5%, 6.5%, 0.2%, respectively. The median follow-up after tomotherapy was 19.86 months. Median survival was 20 months. The 2-year OS was 39.1%. Conclusions : The relatively high dose tomotherapy alone for patients with a recurrent bronchial stump mass which was proximal to the heart demonstrated favorable clinical results without severe heart or pulmonary complications.